(untitled) (East West Medical College Journal, 2026)
Introduction: Many people in Bangladesh are getting dengue and chikungunya, which are significant health problems. Aedes mosquitoes spread both viruses. Dengue has been a constant problem in Bangladesh since 2000. In 2017, there was a big outbreak of chikungunya, and the virus has been spreading ever since. It might be hard to tell the difference between dengue virus (DENV) and chikungunya virus (CHIKV) infections since their symptoms are so similar. Nonetheless, information about the co-circulation of DENV and CHIKV is scarce. Objective: To determine the prevalence and seasonal trends of dengue and chikungunya virus infections among patients presenting with fever in 2025. Methods: This retrospective cross-sectional study used a consecutive sampling method. Data were collected from laboratory records at the Ibn Sina Diagnostic & Consultation Center in Uttara. Both immunochromatographic tests (ICT) and polymerase chain reaction (PCR) assays were used to diagnose DENV and CHIKV. Results: A total of 31,839 samples were analyzed. Of these, 25,939 were tested for dengue and 5,900 for chikungunya. In the dengue group, 15% tested positive for DENV and 85% tested negative. In the chikungunya group, 18% were positive for CHIKV and 82% were negative. The dengue group included 15, 071 (58. 1%) males and 10, 868 (41. 9%) females, with a male-to-female ratio of 1. 39: 1 and a mean age of 25. 25.12 ± 0. 55 years (range: 1– 82 years). The chikungunya group comprised 3, 174 (53. 8%) males and 2, 726 (46. 2%) females, with a male-to-female ratio of 1. 16: 1 and a mean age of 34. 34.40 ± 1. 30 years (range: 3–77 years). The highest number of dengue- positive cases occurred from September to November, accounting for approximately 79. 85% of cases. The peak frequency of sCHIKV was observed from September to October, at approximately 76. 46%. Seasonal variation in positive and negative cases for both viruses was statistically significant (p < 0.0001). Comparisons between peak and off- peak months also revealed statistically significant differences for both viruses (DENV: p < 0. 0001, OR 11. 11.89, 95% CI 3. 21– 44.03. 03; CHIKV: p < 0. 0001, OR 16. 24, 95% CI 3. 3.541–74. 74.64). These findings indicate that dengue and chikungunya infections are no longer restricted to the monsoon season but occur year-round, with the highest incidence in the post-monsoon period. EWMCJ Vol. 14, No. 2, July 2026: 234-244